The Role Of National Leadership And Telecommunication Technology In Finance-Growth Nexus: Evidence From Developing Countries - Salisu, Mannir (2020)
A growing body of economic growth literature suggest that it is essential to emphasise financial development in order to accelerate the process of economic growth. This research investigates the effects of national leadership and telecommunication technology on the finance-growth nexus using balanced panel data from 50 developing countries for the 1997-2017 period. The study employs a set of non-stationary panel data, namely, panel cointegration, and panel cointegrating estimator – Group Mean Fully Modified OLS (GM-FMOLS) to investigate the coefficients and long-run relationships between the variables of interest. The findings show that there is a long-term relationship between the variables wherein financial development, ICT, and quality of national leadership were found to have significant positive impact on economic growth in developing countries. This implies that financial development, telecommunication technology, and the quality of national leadership are important factors for promoting growth. Moreover, the results suggest that the effects of financial development on economic growth is contingent on the quality of national leadership and the sophistication of telecommunication technology in developing countries. The interaction term and marginal effects computed are positive and significant at all levels of ICT as well as on the quality of national leadership.